The Regional Role of the Eurasian Development Bank in the Post-Coronavirus World - A. V. Kuznetsov (Мир новой экономики, 2021)
Until now, the processes of global regionalisation have not been adequately reflected in the formation of systemic approaches to the management of financial relations within the Eurasian Economic Union. It leads to the search for new financial policy mechanisms necessary to stimulate the economies of the EAEU countries in the context of emerging economic and geopolitical constraints, as well as the creation of the necessary prerequisites for industrial cooperation in the context of anti-Russian sanctions and de-globalisation trends intensified by the COVID-19 pandemic. Currently, the vulnerability of the economies of the EAEU member states is due to their extreme dependence on external extra-regional demand, international capital and technology markets, as well as international settlement and payment systems based on the US dollar. The study is based on a dialectical approach. In conducting the research, we used general scientific methods of analysis, synthesis, generalisation, as well as methods of systemic, historical-logical and comparative analysis. The contradictory nature of the development of the world economy at the present stage was revealed. The role of the EDB in creating conditions for sustainable development of the EAEU member states has been substantiated. Changes in the structure of the EDB’s investment portfolio were analysed. The advantages and disadvantages of the EDB’s current activities in the context of the implementation of the Bank’s Strategy for 2018–2020 were summarised. Comparative characteristics of financing of EDB member countries through multilateral development banks were presented. The impact of the COVID-19 coronavirus pandemic on the current and future activities of the EDB was shown.